CULTURAL IDENTITY OF DIASPORIC JAVANESE MUSLIMS OF PONOROGO IN MALAYSIA: CONTINUITY AND CHANGE - Arik Dwijayanto; Yusmicha Ulya Afif (IAIN Manado, 2023)
Abstract: This research seeks to explain the cultural changes and identity in diasporic experience among Javanese Muslims of Ponorogo in Johor, Malaysia. Stuart Hall's perspective on cultural identity and diaspora stress that these are significant concerns for anyone struggling the identity. This paper also examines the notions of a homeland the Javanese Muslims of Ponorogo diaspora in Johor, Malaysia, has held over the past 110 years. What do these notions entail, which developments were essential to their continuity and change, and in what way are current notions of a homeland related to the present-day status and position of the Javanese Muslims of Ponorogo the local society? The cultural changes of the Ponorogo Muslims diaspora in Johor maintained their cultural identity and social harmony with the local society. This research aims to look further at the negotiation process of cultural identity among Ponorogo Muslims in their tradition. The tradition is a cultural dialectics of Javanese and Malay culture. Even these traditions are dynamically changing to be simplified, the essence of their cultural tradition is not affected. Internally, in Johor, sometimes there are other traditions, but they do not take their Javanese identity off. Key Words : Identity, Tradition, Ponorogo Muslims. Abstrak: Penelitian ini berusaha menjelaskan perubahan budaya dan identitas dalam pengalaman diaspora di kalangan Muslim Ponorogo di Johor, Malaysia. Dalam perspektif Stuart Hall tentang identitas budaya dan diaspora menekankan bahwa hal ini menjadi perhatian penting bagi siapa pun yang berupaya untuk mempertahankan identitas tersebut. Tulisan ini juga mengkaji konstruksi gagasan ‘tanah air’ bagi diaspora Muslim Ponorogo di Johor, Malaysia, selama 110 tahun terakhir. Apa yang terkandung dalam gagasan-gagasan tersebut dan bagaimana perkembangan bagi kesinambungan dan perubahannya, serta dengan cara apa gagasan-gagasan tentang tanah air terkait dengan status dan posisi kaum Muslim Jawa Ponorogo saat ini dalam masyarakat setempat? Perubahan budaya diaspora Muslim Ponorogo di Johor mempertahankan identitas budaya dan keharmonisan sosial mereka dengan masyarakat setempat. Penelitian ini bertujuan untuk melihat lebih jauh proses negosiasi identitas budaya umat Islam Ponorogo dalam tradisinya. Tradisi tersebut merupakan dialektika budaya dari budaya Jawa dan Melayu. Bahkan tradisi-tradisi ini secara dinamis berubah menjadi disederhanakan, esensi tradisi budaya mereka tidak terpengaruh. Secara internal, di Johor, terkadang ada tradisi lain, tetapi tidak menghilangkan identitas Jawanya. Kata Kunci : Identitas, Tradisi, Muslim Ponorogo.